2008
DOI: 10.1242/jcs.025031
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein β deficiency provides cerebral protection following excitotoxic injury

Abstract: The CCAAT/enhancer-binding protein β (C/EBPβ, also known as CEBPB) was first identified as a regulator of differentiation and inflammatory processes in adipose tissue and liver. Although C/EBPβ was initially implicated in synaptic plasticity, its function in the brain remains largely unknown. We have previously shown that C/EBPβ regulates the expression of genes involved in inflammatory processes and brain injury. Here, we have demonstrated that the expression of C/EBPβ is notably increased in the hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 57 publications
9
76
0
Order By: Relevance
“…Despite considerable progress in excitotoxic research and antiexcitotoxic drug therapies, few studies have investigated the mechanisms and potential treatment strategies focused on excitotoxic-induced cognitive impairment. Previous work by our laboratory and others has demonstrated that inflammation and oxidative stress play important roles in the pathological process of excitotoxic-induced cognitive impairment (5,10,33). Consistent with a recent report, we have shown that DA treatment significantly stimulates the release of proinflammatory cytokines such as IL-1b, TNF-a, Cox-2, and iNOS, and induces astrocytic activation by upregulating C/EBP b expression in the hippocampus of mice (10).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Despite considerable progress in excitotoxic research and antiexcitotoxic drug therapies, few studies have investigated the mechanisms and potential treatment strategies focused on excitotoxic-induced cognitive impairment. Previous work by our laboratory and others has demonstrated that inflammation and oxidative stress play important roles in the pathological process of excitotoxic-induced cognitive impairment (5,10,33). Consistent with a recent report, we have shown that DA treatment significantly stimulates the release of proinflammatory cytokines such as IL-1b, TNF-a, Cox-2, and iNOS, and induces astrocytic activation by upregulating C/EBP b expression in the hippocampus of mice (10).…”
Section: Discussionsupporting
confidence: 92%
“…Excitotoxic brain damage is considered to be one of the major mechanisms by which neurons of the CNS die and can result in memory decline. Excitotoxicity may also be involved in the pathogenesis of many brain disorders, including brain ischemia, epilepsy, traumatic brain injury, and neurodegenerative diseases such as multiple sclerosis, Alzheimer's disease, amyotrophic lateral sclerosis, Parkinson's disease, and Huntington's disease (5,10,33,45). Despite considerable progress in excitotoxic research and antiexcitotoxic drug therapies, few studies have investigated the mechanisms and potential treatment strategies focused on excitotoxic-induced cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations